2023
DOI: 10.3390/nu15092025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutritional Interventions in Older Adults with Malnutrition or at Risk of Malnutrition on Muscle Strength and Mortality: Results of Pooled Analyses of Individual Participant Data from Nine RCTs

Abstract: Nutritional intervention studies in older adults with malnutrition aim to improve nutritional status. Although these studies show a significant gain in body weight, there is inconsistent evidence of clinical effectiveness on muscle strength and mortality. This study aimed to examine the effects of nutritional interventions on muscle strength and risk of mortality in older adults (malnourished or at risk) and explore whether these effects are influenced by participant characteristics. Individual participant dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…However, a systematic review and meta-analysis has shown that nutritional interventions, such as oral nutritional supplements, dietary counselling, or a combination of both, do not lead to improvements in HGS in older adults who are malnourished or at risk of malnutrition. [52]. More research is needed to verify the efficacy of the proposed nutritional interventions on HGS and other clinically relevant outcomes in people who survive COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review and meta-analysis has shown that nutritional interventions, such as oral nutritional supplements, dietary counselling, or a combination of both, do not lead to improvements in HGS in older adults who are malnourished or at risk of malnutrition. [52]. More research is needed to verify the efficacy of the proposed nutritional interventions on HGS and other clinically relevant outcomes in people who survive COVID-19.…”
Section: Discussionmentioning
confidence: 99%